Effects of Light Color on Consumers' Acceptability and Willingness to Eat Apples and Bell Peppers. Issue 1 (25th November 2015) - Yang, Famous Lue; Cho, Sungeun; Seo, Han‐Seok
Abstract : Abstract: This study aimed to determine whether ambient light colors affect consumers' willingness to eat, sensory perceptions and hedonic impressions of foods. Sliced apples and red bell peppers were presented under five different colors of light: white, yellow, green, blue and red, respectively. Participants were asked to observe the presented food under these colored lights, to rate their willingness to eat and liking of food appearance. After tasting, participants were asked to rate intensities of flavor and crispness and rate overall impression of the food. When the food samples were presented under white or yellow light rather than blue light, participants not only wanted to eat more, but also liked the foods more. Participants were especially more willing to eat apples under yellow light than under white light commonly experienced in daily life. Flavor intensity of apples was found to be lower under blue light than under yellow, white or red light; this trend was not observed in flavor intensity of bell peppers. Crispness intensities were not different among the five light‐color conditions. In conclusion, our findings support and extend the notion that light colors modulate consumers' willingness to eat and their hedonic impressions of foods, especially apples and bell peppers. Practical Applications: As multicolored light‐emitting diode bulbs have become popular, foods and drinks are often displayed under colored light in restaurants and retail stores. The results of this study will provide sensory scientists and food‐service professionals with valuable insights as to how their consumers will most likely behave under colored lights in a given dining establishment. In addition, based on findings that participants' appetites were significantly higher for apples under yellow light than under white light, yellow light might be used as a tool for encouraging people to consume more apples in everyday life.